Pengalaman Penderita DM Tipe 2 yang Mengikuti Program Pengelolaan Penyakit Kronis (Prolanis) dalam Mengendalikan Kadar Glukosa Darah di Puskesmas - Nandang Jamiat; Salami Salami; Pipit Pitriani (Jurnal Medika Cendikia, 2017)
Diabetes Mellitus (DM) disease that is not immediately treated will cause various acute and chronic complications. Indonesia developed a DM prevention program called a chronic disease management programme. Prolanis is a system of health services and an integrated proactive approach that is implemented in an integrated manner involving participants, health facilities, and Badan Penyelenggara Jaminan Sosial(BPJS)especially health area. The purpose of this study was to determine the meaning of experience of type 2 DM patients who follow Prolanis. Six participants were taken using purposive sampling. The results of the study identified three themes: (1) knowledge concept of DM, (2) how to treat DM type 2, (3) type of drug and its benefits. DM patients become more aware of how to care, and this needs to get support from the health department through Puskesmas.